Influence of Nitrogen Applications on Seed Yield and Chemical Ingredient of Winter Rapeseed - KARAASLAN, DAVUT; SURUCU, ABDULKADIR; DORAN, ILHAN; YILDIRIM, MEHMET (Asian Journal of Chemistry, 2010)
In this experiment, it was purposed to investigate effects of different nitrogen applications on seed yield, oil and protein content and nutrient uptake of winter rapeseed grown at field conditions. Three cultivars of winter rapeseed (Brassica napus L.) askona, karola and silvia, were used. The nitrogen applications applied to the soil were 0, 60, 120 and 180 kg N ha-1 as ammonium sulfate. Nitrogen concentration increased seed yield compared to untreated plants in all three cultivars. The highest seed yield was obtained from the plants received the highest nitrogen rate (180 kg N ha-1) for all three cultivars. When compared to seed yield of cultivars, the highest seed yields was in cultivar, askona with 180 kg N ha-1 and the lowest one was in the askona without nitrogen application too. The protein contents in all three cultivars were increased with the highest nitrogen content compared to untreated plants. However other nitrogen applications did not change protein content consistently. The changes in oil content were also not consistent among nitrogen levels and cultivars. Different nitrogen doses resulted in changes in nutrient levels in leaves of all three cultivars in some way. It can be revealed that nitrogen application at right doses can increase seed yield, oil and protein contents by increasing macro and micro nutrition of plants.